Essential descriptors for mycotoxin contamination data in food and feed. (February 2022) - Mesfin, Addisalem; Lachat, Carl; Vidal, Arnau; Croubels, Siska; Haesaert, Geert; Ndemera, Melody; Okoth, Sheila; Belachew, Tefera; Boevre, Marthe De; De Saeger, Sarah; Matumba, Limbikani
Graphical abstract: Highlights: Delphi method constructed consensus among experts on mycotoxin data descriptors. Modularizing and organizing descriptors as a data submission template was relevant. The proposed descriptors ensure harmonization of mycotoxins contamination data. More descriptors identified in relation to pre and post-harvest practices of crops. Abstract: Mycotoxin food contamination data is scattered, isolated, and poorly described. Reporting mycotoxin contamination data in a standardized manner is essential for collaborative research and integrated large-scale data analysis. The present study aimed to complement the existing European Food Safety Authority (EFSA) and Global Environment Monitoring System (GEMS) mycotoxin contamination data descriptors for application in low- and middle-income countries in particular. A three-round Delphi process was followed to establish a consensus on the missing descriptors. An invitation letter was first sent to 34 mycotoxin experts of an international collaboration of MYTOX-SOUTH®, of which 12 finally participated in the study. The response rate was 29.4% (10/34) in the Delphi I, 75% (9/12) in the Delphi II, and 83.3% (10/12) in the Delphi III rounds. The majority of the Delphi study participants were professors from 6 universities. Twenty-two descriptors (17 study level, 1 sample level, and 4 assay level) were proposed and were mainly related to pre and post-harvest periods of a food/feed sample. The pre-defined (>70% in the Delphi II and > 80% in the Delphi III) agreement among participants was achieved for all the proposed descriptors. The existing descriptors from EFSA (33) and GEMS (25) with the new proposed MYTOX-SOUTH® (22) descriptors, in total 80 descriptors, were arranged as study, sample, and assay categories and organized as a data submission template. Pre-testing of the template on three mycotoxin researchers indicated that the average time to fill out the form for a sample was 42 min. The current format helps mycotoxin contamination data to become more informative, reusable, and applicable especially to data from low- and middle-income countries. The above-proposed descriptors will help GEMS to provide technical cooperation with countries wishing to initiate and strengthen food contaminant monitoring programs. Similarly, the descriptors from the current study will be useful for EFSA as it regularly updates the Standard Sample Description. A standardized global reporting format for mycotoxin contamination data will enable national authorities to perform mycotoxins exposure and risk assessments and share data for international benchmarking. Standardized reporting and sharing of mycotoxin contamination data should be further advocated in ongoing research and become common practice in authorities, companies, academia, and other entities working on mycotoxin in food and feed.